Informed consent practice for obstetric and gynaecologic procedures: A patients' perspective from a developing country. Issue 3 (28th February 2019) - Zeeshan, Muhammad F.; Yousufi, Zainab; Khan, Durdana; Malik, Farhat R.; Ashfaq, Fizza; Batool, Fatima; Atta, Lyaba; Tariq, Hira; Huma, Zille; Ghafoor, Rahat; Jamil, Ayisha; Qazi, Umair
Abstract: Objectives: To assess the surgical informed consent (SIC) practices for obstetric and gynaecological (OB‐GYN) procedures at different hospitals in Pakistan. Methods: Study was conducted in five hospitals (three public and two private) of Peshawar, Pakistan. A pretested structured tablet‐based questionnaire was administered from October 2016 through January 2017 among post‐op OB‐GYN patients. Results: About 27% of the patients (significantly more in private hospitals, P = 0.001) did not remember a formal consent administration. Most patients (80%) felt they had no choice about signing the consent. About 65% (mostly in public as compared with private hospitals) mentioned that they would have signed it regardless of the specifics in it ( P < 0.001). Patients had increased odds to recall consent if they felt empowered, odds ratio (OR) = 4.5; had an opportunity to ask questions, OR = 7.2; wanted more explanation, OR = 2.8; and had consent administered in their mother tongue, OR = 6.9. Discussion: Patients' recall of key elements of consent was low. The time spent with the patient for consenting was much shorter than recommended. The printed consent forms were mostly not available in patients' mother tongue. Conclusions: Consent practice for OB‐GYN procedures was suboptimal in studied hospitals. Patients' attitude toward informed consent practices largely reflected providers' focus on obtaining a legally valid signed consent as opposed to administering a consent that empowers patients to make an informed decision in the absence of any external pressure.